Theater, Music and Memory in the Teatrosamba do Caixote (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
Mnemonic box is a concept used by Aleida Assmann to refer to a portable space of memories. In its complex role as a boundary between scene and audience, as well as a stool for musicians and actors, the box, imbued with memories, is also a mnemonic box, a container of the experiences and processes of the Teatrosamba do Caixote. A theatrical device within the samba circle, this activity conceived by the Grupo dos 7 was part of the City in City Out Project, implemented in spaces in the North Zone of São Paulo between 2001 and 2004. This article explores the contents of this memory box to outline an expository itinerary of the Teatrosamba do Caixote’s journey during that period.
Keywords: theater; music; memory; theatrical Archives; G7